Vertex algebra constructions for (analytic) geometric Langlands in genus zero - Davide Gaiotto (Journal of High Energy Physics)
Abstract We employ two-dimensional chiral algebra techniques to produce solutions of certain differential and integral equations which occur in the context of the Analytic Geometric Langlands Program. In particular, we build “Multiplication Kernels” K 3(x, x′, x′′) which intertwine the action of s l 2 $$ \mathfrak{s}{\mathfrak{l}}_2 $$ Gaudin Hamiltonians on three sets of variables.